Effects of lysosomal iron involvement in the mechanism of mitochondrial apoptosis on postmortem muscle protein degradation. (30th October 2020) - Zhang, Jiaying; Yu, Qunli; Han, Ling; Han, Mingshan; Han, Guangxing
Highlights: Lysosomal iron induces ROS accumulation and lysosomal membrane destabilization. Mitochondrial membrane is damaged caused by iron-induced ROS generation. Lysosomal iron triggers Bid and cytochrome c released from mitochondria. Iron-dependent caspases activation of bovine muscle during postmortem aging. Lysosomal iron involvement in apoptosis improves muscle protein degradation. Abstract: This study investigated the effect of lysosomal iron involvement in the mechanism of mitochondrial apoptosis on bovine muscle protein degradation during postmortem aging. Six crossbred cattle were studied to evaluate intracellular reactive oxygen species (ROS), antioxidant enzyme activity, lysosomal membrane stability, mitochondrial dysfunction-induced apoptosis, desmin and troponin-T degradation in both control and iron chelator desferrioxamine (DFO) groups. Results showed that lysosomal iron induced ROS accumulation and lysosomal membrane destabilization by decreasing the antioxidant enzyme activity ( P  < 0.05). Subsequently, lysosomal dysfunction mediated by iron increased mitochondrial membrane permeability and decreased mitochondrial membrane potential, thereby enhancing Bid and cytochrome c release and caspase-9/-3 activation ( P  < 0.05). Ultimately, lysosomal iron mediated lysosomal-mitochondrial apoptosis increased the postmortem bovine muscle desmin and troponin-T degradation ( P  < 0.05). The results indicated that lysosomal iron contributes to postmortem meat tenderization through the lysosomal-mitochondrial dysfunction-induced apoptosis pathway.